The Effect Of Entrepreneurial Orientation On Marketing Performance Of Street Food MSMEs In Pontianak City With Product Innovation as a Mediation - Andrean; Lie Heng (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2025)
This study investigates the impact of entrepreneurial orientation on the marketing performance of Street Food MSMEs with product innovation as an intermediary. This study uses a quantitative method with an associative approach. Data were collected from 140 street food MSMEs from a population of 245 businesses selected using a purposive sampling technique, with the criteria of having been operating for at least three years and having a fixed/semi-fixed location. Data analysis used Structural Equation Modeling (SEM) with AMOS software. The results showed that entrepreneurial orientation had a significant positive effect on product innovation (0.531; p